2016
DOI: 10.3389/fmars.2016.00044
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance Curves of Functional Traits Aid Understanding of Thermally Induced Changes in Diatom-Mediated Biogeochemical Fluxes

Abstract: How the functional traits (FTs) of phytoplankton change with temperature is important for understanding the impacts of ocean warming on phytoplankton mediated biogeochemical fluxes. This study quantifies the thermal performance curves (TPCs) of FTs in the cosmopolitan model diatom, Thalassiosira pseudonana, to advance understanding of trade-offs between physiological (photoacclimation, carbon fixation, nitrate, phosphate, and silicate uptake) and morphological traits (cell volume and frustule silicification). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 53 publications
(66 reference statements)
8
43
0
Order By: Relevance
“…A previous study (Baker et al, 2016) has found that nutrient uptake rates are highest at intermediate temperatures. A previous study (Baker et al, 2016) has found that nutrient uptake rates are highest at intermediate temperatures.…”
Section: Temperature Dependence Of Nutrient Requirements and Competitmentioning
confidence: 85%
“…A previous study (Baker et al, 2016) has found that nutrient uptake rates are highest at intermediate temperatures. A previous study (Baker et al, 2016) has found that nutrient uptake rates are highest at intermediate temperatures.…”
Section: Temperature Dependence Of Nutrient Requirements and Competitmentioning
confidence: 85%
“…(), respectively, as described in Baker et al. (). Net flux was calculated as the difference between nutrient concentrations normalized to cell abundance at the start and end of the exponential phase.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was discarded and cell pellets stored frozen at −80°C until extraction and later analysis as previously described in Baker et al. (). Samples were extracted in 3 mL volume of 3:2 90% acetone: 100% dimethyl sulfoxide extraction reagent in the dark at 4°C for 15 min (Shoaf and Lium ).…”
Section: Methodsmentioning
confidence: 99%
“…The thermal reaction norm for population growth depends on the temperature dependences of enzyme activities (Corkrey et al, 2014;Ratkowsky, Olley, & Ross, 2005), and few processes or pathways within the cell should be immune to the effects of directional temperature selection (Baker et al, 2016;Nedwell, 1999;Padfield et al, 2015;Schaum et al, 2017). Depending on the genes affected, changes in growth rate may be accompanied by changes in traits not directly associated with the thermal reaction norm.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the genes affected, changes in growth rate may be accompanied by changes in traits not directly associated with the thermal reaction norm. For example, stoichiometry may respond to thermal adaptation due to changes in relative resource requirements of phytoplankton cells, which in turn may affect species' competitive abilities (e.g., for N and P) and ultimately global biogeochemical cycles (Baker et al, 2016;Litchman, Klausmeier, Schofield, & Falkowski, 2007;Redfield, 1958). An increase in maximum growth rate at the selection temperature may lead to a decrease in affinity for a given nutrient due to a trade-off between allocation of cellular resources to reproduction versus nutrient uptake (Grover, 1991;Klausmeier, Litchman, Daufresne, & Levin, 2004).…”
Section: Introductionmentioning
confidence: 99%